Peran Kredibilitas Merek Memediasi Pengaruh Kredibilitas Endorser Terhadap Ekuitas Merek - Cut Devi Maulidasari; Damrus Damrus; Cici Darmayanti (universitas teuku umar, 2022)
The purpose of this study was to examine the role of endorser credibility on brand equity. How to mediate brand credibility also supports this role. This study uses a qualitative approach by using secondary data in the form of literature and literature study. The results of this study show that brand credibility has actually become a mediation that can be used on endorser credibility and brand equity. This study states that an endorser must be someone who has been declared competent and credible, has attractiveness, ability or skill, and trust. The credibility of the endorser is believed to be able to develop the credibility of the brand.. Keywords: Brand Equity, Endorser, Brand Credibility, Celebrity